Clinicopathologic characteristics, therapeutic modalities and survival outcomes of plasmablastic lymphoma: A real-world study - Yan-Hua Zheng; Kun Xie; Hong-Yuan Shen; Zhuo Wan; Shan Gao; Wen-Rui Sun; Guang-Xun Gao; Li Liu; Juan Feng (Archives of Medical Science, 2021)
Introduction Plasmablastic lymphoma (PBL), an extremely rare subtype of B-cell non-Hodgkin lymphoma (NHL), is characterized by aggressiveness, rapid progression and a bleak prognosis. Neither a standardized regimen nor a consensus for PBL treatment has been established.